The effect of education of self care behaviors based on family-centered empowerment model in type II diabetes - Ghotbi, narghes; Seyed Bagher Maddah, sadat; Dalvandi, asghar; Arsalani, narghes; Farzi, marjan (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Type II diabetes, can be controlled by medical treatment and self care behaviors, however the patients often fail to comply with self care behaviors. Concerning the role of family in supporting patients’ self care behaviors, the aim of this study is to determine the effect of a family –centered education of self care behaviors based on family- centered empowerment model on patients with type II diabetes. Methods and materials: The quasi-experimental design carried out on 40 patients with type II diabetes who were randomly assigned to intervention and control groups. The education of self care behaviors in four domains (nutrition, physical activity and exercise, medications, complications and foot care) for intervention group and their families was performed. Data were collected by a valid and reliable questionnaire. The scores of self care behaviors before and after the education were measured. Data were analyzed by the SPSS16 software. Findings: Prior to education, there was no significant difference between self-care behaviors scores in both intervention and control groups (p>0/05). After education, self-care behaviors of the intervention group in total scores and also in all domains were increased and statistically were significant (p <0/05), while there was no significant change in the control group. Conclusion: The findings showed that this education method improved self -care behaviors among patients with type II diabetes. These results can be used in the other chronic diseases and different levels of nursing care. Keywords: Education, family-centered empowerment model, diabetes, self-care REFERENCES Alhany F (2004). [ Design and evaluation of family- centered empowerment model for prevention of iron deficiency], Ph. D Thesis in Nursing. Univercity of Tarbiat Modares, 2004. (Persian). American Diabetes Association(2004). Diagnosis and classification of diabetes mellitus. Diabetes Care. 27(1)5-10. Atak N, Kose k, GurkanT(2008). The impact of patient education on diabetes empowerment scale (DES) and diabetes attitude scale(DAS-3) in patients with type 2 Diabete. Turkish Journal of Medical Sciences. 38 (1) 49-57. Ayele K, Tesfa B,et al (2012). Self care behavior among patients with diabetes in Harari, Eastern Ethiopia: The health belief model perspective. Public Library of Science One. 7(4) 1-6. Centers for Disease Control and Prevention (2011). National diabetes fact sheet: national estimates and general information on diabetes and prediabetes in the United States, 2011. Atlanta, GA: U. S. Department of Health and Human Services, Centers for Disease Control and Prevention. 1-12. Ding CH, Teng CL, Koh CN(2006). Knowledge of diabetes mellitus among diabetic and non-diabetic patients in Klinik Kesihatan Seremban. The Medical journal of Malaysia. 61(4) 399-404. Farsi Z, et al(2009). [Application of health belief model in change of self care behaviors of diabetic patients]. Iran Journal of Nursing . 22(61)61-72(persian). Funnell MM, Anderson R. M(2004). Empowerment and self management of diabetes. Clinical diabetes . 23(3) 123-7. Gallegos EC, Ovalle-Berumen F, Gomez-Meza MV(2006). Metabolic control of adults with type 2 diabetes mellitus through education and counseling. Journal of Nursing Scholarship . (4) 344-51. Garcia-Huidobro D, et al(2011). Family intervention to control type 2 diabetes: a controlled clinical trial. Family Practice . 28 (1)4-11. Hamadzadeh S,et al(2013) [Coping styles and self care behaviors among diabetic patients]. Iran Journal of Nursing . 25 (80) 24-33. (persian). Harvey JN, Lawson VL(2008). The importance of health belief models in determining self-care behavior in diabetes. Diabetic Medicine . 26(1)5-13. Helgeson VS, Becker D, Mellon C(2008). Parent and adolescent distribution of responsibility for diabetes self care: links to health out comes. Pediatric psychology . 33(5)497-508. Heydari SH, et al (2009). [ Research in Nursing]. 1rst edition. Tehran, Nursing Organization of Islamic Republic of Iran publication (Persian). Jafarian N, Heydari A(2000). [The role of health belifes in the adoption insulin in diabetic patients attending the diabetes reaserch center of Hamadan]. Scientific Journal of HamadanUniversity of Medical Science . 7(4) 54-59(persian). Kang CM, et al(2010) Comparison of family partnership intervention care vs. conventional care in adult patients with poorly controlled type 2 diabetes in a community hospital: a randomized controlled trial. International journal of nursing studies . 47(11): 1363-73. Keogh KM, et al(2007) changing illness perceptions in patient with poorly controlled type 2 diabetes, a randomised control trial of a family – based intervention: protocol and pilot study. BioMed Central Family Practice . 8(36)1-10. Koshyar H(2009). [Nursing Theory and Theorists]. 1rst edition. Tehran, Andishe Rafi publication. (Persian). MalekGavgani R, Poursharifi H, AliasgarzadehA(2010). Effectiveness of information-motivation and behavioral skill (IMB) model in improving self-care behaviors & Hba1c measure in adults with type2 diabetes in Iran-Tabriz. Procedia Social and Behavioral Sciences . 5: 1868–1873. Mardani Hamuleh M, Shshraki Vahed A(2010). [ Effect of education based on health belife model on adherence to the diabetic diet]. Iranian Journal of Diabetes and Lipid Disorder . 9(4): 268-275. (Persian). Masoudi R,et al(2010) [The effect of family centerd empowerment model on the quality of life in erderly people]. Journal of Qazvin University of Medical Sciences. 14(1) 57-64. Osborn CY, Fisher JD(2008). Diabetes education: integrating theory, cultural considerations and individually tailored content. Clinical Diabetes . 26(4) 148-50 Otero LM, Zanetti ML, OgrizioMD(2008). Knowledge of diabetic patients about their disease before and after implementing a diabetes education program. Revista Latino-America de Enfermagem . 16(2): 231-7. Schoen berg NE,et al(2008). Diabetes self care among a multiethnic sample of older adults. Journal of Cross Cultural Gerontology . 23(4) 361-76. Shaw JE, Sicree RA, Zimmet PZ(2010). Global estimate of the prervalence of diabetes for 2010 and 2030. Diabet Reaserch and Clinical Practice . 87(1) 4-14. Shirazi M, Anoosheh M, Rajab A(2011). [The effect of self care program education by group discussion method on self concept in diabetic adolescent girls reffered to Iranian Diabetes Society]. Iran Journal of Nursing Research. 6(22) 40-52.(persian. ( Tang TS, et al (2010). Self-management support in “real-world” settings: An empowerment-based intervention. Patient Education and Counseling. 79(2) 178–184. Teufel-Shone N, Drummond R, Rawiel U(2005). Developing and adapting a family-based diabetes program at the U. S. -Mexico border. Preventing Chronic Disease . 1(2) 1-9. Tolouei M, et al(2006). [Motivational factors of nurses in the education of patients]. Hayat . 12(2) 43-51. (persian). Vahedian- Azimi A(2009). [Effect of family-centered empowerment model on the life style of myocardial infarction patients]. Iranian Journal of Critical Care Nursing . 2(4) 127-32. (persian).